Interview with Leon Botstein (Bard College) - Leon Botstein (Voprosy obrazovaniya / Educational Studies Moscow, 2015)
Leon Botstein is President of Bard College, Director of the American Symphony Orchestra, and Board Chairman of the Central European University. He is also an accomplished musicologist and historian of education. Among his publications on education is his book, Jefferson’s Children: Education and the Promise of American Culture. The following interview took place in Moscow, on April 1, 2015, when Dr. Botstein was in Russia to conduct the Russian National Or-chestra’s performance of pieces by Prokofiev and Bartok at the Tchaikovsky Concert Hall the following day.